Suluk Wujil: Model of Normatif-Spiritual Management in Islamic Education - Hafidl, Noor; Purwanto, Purwanto; Suharto, Toto (QUALITY, 2024)
The present study offers an analytical review of the content of Suluk Wujil, entitled "Normative-Spiritual Management of Islamic Education." An understanding of the values espoused in Suluk Wujil can contribute to the advancement of pragmatic science in real-life contexts, particularly in the field of Islamic education, which must continue to innovate and identify itself. The objective of this article is to make a contribution to the field of spiritual normative management science in an era of accelerated progress and heightened complexity. This qualitative descriptive research aims to elucidate the mystical concept of Sunan Bonang and reconstruct the cultural mindset that provides the background. The findings of this study indicate that Suluk Wujil encompasses normative spiritual values that can be integrated into conventional management systems, specifically those related to planning, leading, organizing, and controlling. These four management systems can be compared with the spiritual values contained in Suluk Wujil Sunan Bonang, which reads, "al Hayatu bila Nafsin, an Nadloru bila 'Ainin, as Sam'u bila Udlunin dan al Qadaru bila 'A'dloi." In general, the meaning of spiritual normative management will be more effective and efficient in building an organizational climate that is comfortable and focused on achieving goals.Suluk Wujil: Model Manajemen Normatif-Spiritual dalam Pendidikan Islam. Penelitian ini menawarkan tinjauan analitis terhadap isi Suluk Wujil, yang berjudul “Manajemen Normatif-Spiritual Pendidikan Islam.” Pemahaman tentang nilai-nilai yang dianut dalam Suluk Wujil dapat memberikan kontribusi bagi kemajuan ilmu pengetahuan pragmatis dalam konteks kehidupan nyata, khususnya di bidang pendidikan Islam, yang harus terus berinovasi dan mengidentifikasikan dirinya. Tujuan dari artikel ini adalah untuk memberikan kontribusi pada bidang ilmu manajemen normatif spiritual di era yang semakin cepat dan kompleks. Penelitian deskriptif kualitatif ini bertujuan untuk menjelaskan konsep mistik Sunan Bonang dan merekonstruksi pola pikir budaya yang melatarbelakanginya. Temuan dari penelitian ini menunjukkan bahwa Suluk Wujil mencakup nilai-nilai spiritual normatif yang dapat diintegrasikan ke dalam sistem manajemen konvensional, khususnya yang terkait dengan perencanaan, kepemimpinan, pengorganisasian, dan pengendalian. Keempat sistem manajemen tersebut dapat dibandingkan dengan nilai-nilai spiritual yang terkandung dalam Suluk Wujil Sunan Bonang, yang berbunyi, “al Hayatu bila Nafsin, an Nadloru bila ‘Ainin, as Sam'u bila Udlunin dan al Qadaru bila ’A'dloi.” Secara umum, makna manajemen normatif spiritual akan lebih efektif dan efisien dalam membangun iklim organisasi yang nyaman dan fokus pada pencapaian tujuan.